A population-based study identifies an association of THBS2 with intervertebral disc degeneration. Issue 10 (October 2019) - Deguchi, T.; Hashizume, H.; Nakajima, M.; Teraguchi, M.; Akune, T.; Yamada, H.; Tanaka, S.; Yoshimura, N.; Nojima, M.; Yoshida, M.; Ikegawa, S.
Summary: Objective: To clarify the genetic mechanisms underlying intervertebral disc degeneration (IDD), we examined the associations between single-nucleotide polymorphisms (SNPs) and indicated as coefficient of interaction term (IDD) in a general population in Japan. Methods: This was a cross-sectional study. In 1, 605 participants, C2-3 to L5/S1 in the total spine magnetic resonance imaging (MRI) were evaluated using the Pfirrmann's scoring system. Disc scores of 4 and 5 were defined as IDD. Eight SNPs in eight genes associated with IDD were examined at each disc level, considering the non-genetic risk factors of age, sex, and body mass index (BMI). Results: The highest odds ratio was found for rs9406328 in the THBS2 gene at disc level T12-L1 (OR 1.27, 95%CI 1.05 to 1.53), and this association was strengthened after adjustment for age using logistic regression (OR 1.37, 95%CI 1.12 to 1.67). Among participants aged <50 years and 50–59, the average IDD score in those with 2 risk alleles of rs9406328 was markedly higher than in those with 0 or 1 risk allele, and the difference is much wider than the elderly participants. It indicates the genetic effect of rs9406328 is stronger in the younger age groups. Finally, multiple linear regression analyses of the association between rs9406328 and IDD, adjusted for age, sex, and BMI at each disc level, showed a statistical interaction between age and the number of risk alleles at C7-T1, T3-4 and T4-T5 as well as T12-L1.results Conclusion: The association between rs9406328 in THBS2 and IDD was replicated. The contributions of genetic and environmental factors to IDD differed by disc level.conclusion